ANALYSIS OF STOCK MARKET REACTION TO LARGESCALE SOCIAL RESTRICTIONS POLICY ANNOUNCEMENT - Aliakito Luckman; Erly Mulyani (Berkala Akuntansi dan Keuangan Indonesia, 2022)
This study aims to analyze stock market reactions to large-scalesocial restrictions policy implementation announcements. Themethod used is event study. This study used 7, 5, and 3 daysevent window and 120 days estimation window for calculatingabnormal return. The samples of this study are 32 companies inthe tourism, hotel, and restaurant sub-sector listed in IndonesiaStock Market which were determined by purposive samplingmethod. The results of this study indicate that 1) there was nosignificant negative market reaction indicated by negative andinsignificant average abnormal return and accumulation averageabnormal return around the announcement date of the Large-ScaleSocial Restrictions (PSBB) policy implementation which meansthat the market does not react to the event and 2) there was nosignificant difference in average abnormal return before and afterthe announcement of the Large-Scale Social Restrictions (PSBB)policy implementation.